The Limits of Memory and the News: Archival Journalism, Law, Ethics, and the Right to be Forgotten - Cetina Presuel, Rodrigo (2022)
The right to be forgotten has been widely discussed from a legal perspective. Courts have analyzed the existence and constitutional compatibility of the right in the national legal order of several jurisdictions around the world. However, even if the right to be forgotten is not a universally recognized right, by understanding how the law approaches tensions that arise between the right to freedom of expression and the rights to seek, impart and receive information, on one hand, and a right to be forgotten, underpinned by the rights to honor, privacy and personal data protection on the other, journalists can extract ethical guidelines that can orient them in the correct use of archival information about individuals to report on current events. This work begins by explaining how legal debates can help inform ethical discussions about journalism. Then, by exploring the legal development and justifications for the right to be forgotten and identifying key elements of this emerging right, we engage in a discussion around the use of archives and memory in journalism and then identify the elements that journalists should consider in relation to the use of archival information in their profession in a way that allows them to fulfill their journalistic duties without ignoring the legal context.